How to tie a scarf : 33 styles. (Potter Style, 2013)
From designer silk squares to chunky homemade knits, this guide is filled with inspired ways to style your scarves. Inside you'll find: Step-by-step tutorials for square, oblong, and embellished scarves ; Styles for the summer, fall, winter, and spring seasons ; DIY scarf accessories featuring camera straps, tote bags, necklaces and more.